THE IMPORTANCE OF MARKETING IN SUPPORTING BUSINESS DEVELOPMENT - Aid Anwar, Raihan; Ramadhan, Rama (Journal for Management Student (JFMS), 2022)
n this era of globalization, business competition is getting tougher, so companies must pay attention to one important aspect in facing this very tight competition, namely marketing. Marketing is a process of planning and developing business activities which includes pricing, promotion and distribution of a number of ideas, goods or services directed at an exchange process that satisfies individual and organizational goals. By using a marketing strategy in running a business, companies are expected to be able to face competition, retain customers, as well as gain new customers for business development for a company.